Association of Telomere Length and Mitochondrial DNA Copy Number in a Community Sample of Healthy Adults - Tyrka, Audrey R. (Exp Gerontol, 2015)
Cellular aging plays a role in longevity and senescence, and has been implicated in medical and psychiatric conditions, including heart disease, cancer, major depression and posttraumatic stress disorder. Telomere shortening and mitochondrial dysfunction are thought to be central to the cellular aging process. The present study examined the association between mitochondrial DNA (mtDNA) copy number and telomere length in a sample of medically healthy adults. Participants (total n=392) were divided into 4 groups based on presence or absence of early life adversity and lifetime psychopathology: No Adversity/ No Disorder, n=136; Adversity/ No Disorder, n=91; No Adversity/ Disorder, n=46; Adversity/ Disorder, n=119). Telomere length and mtDNA copy number were measured using quantitative polymerase chain reaction. There was a positive correlation between mtDNA and telomere length in the entire sample (r=0.120, p<0.001) and in each of the four groups of participants (No Adversity/ No Disorder, r=0.291, p=0.001; Adversity/ No Disorder r=0.279, p=0.007; No Adversity/ Disorder r=0.449, p=0.002; Adversity/ Disorder, r=0.558, p<0.001). These correlations remained significant when controlling for age, smoking, and body mass index and establish an association between mtDNA and telomere length in a large group of women and men both with and without early adversity and psychopathology, suggesting co-regulation of telomeres and mitochondrial function. The mechanisms underlying this association may be important in the pathophysiology of age-related medical conditions, such as heart disease and cancer, as well as for stress-associated psychiatric disorders.